Nutrition status of junior elite Canadian female soccer athletes - Gibson, J. C.; Stuart-Hill, L. A.; Martin, S.; Gaul, C. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
Adolescent female team-sport athletes are faced with the challenge of meeting nutrition requirements for growth and development, as well as sport performance. There is a paucity of evidence describing the dietary adequacy of this population in respect to these physiological demands. Therefore, the aim of this study was to comprehensively evaluate the nutrition status of junior elite female soccer athletes. Method: A total of 33 athletes (15.7 ± 0.7 yr) completed anthropometric assessment, 4-day food records analyzed for macro- and micronutrient intake, and hematological analysis. Energy expenditure was estimated using predictive equations. Results: Mean sum of 7 skinfolds was 103.1 ± 35.2 mm, and body-mass index was 22.7 ± 2.7. Mean energy intake was 2,079 ± 460 kcal/day, and estimated energy expenditure was 2,546 ± 190 kcal/day. Of the athletes, 51.5% consumed Conclusion: A high proportion of players were not in energy balance, failed to meet carbohydrate and micronutrient recommendations, and presented with depleted iron and vitamin D status. Suboptimal nutrition status may affect soccer performance and physiological growth and development. More research is needed to understand the unique nutrition needs of this population and inform sport nutrition practice and research.